Correlation between fracture toughness and constraint of bi‐material interfaces with different mechanical mismatches. Issue 2 (6th November 2022) - Xiao, Jinyong; Wang, Guozhen; Xuan, Fuzhen; Tu, Shantung
Abstract: In this work, the correlation between ductile fracture toughness and a new unified constraint parameter A d * for bi‐material interfaces with different mechanical mismatches (strength and hardening mismatches) has been investigated based on finite element analysis and experimental data validation. The results show that with increasing crack depth (geometric constraint) and mechanical mismatch level (increasing undermatch or overmatch level), the J–R curves and fracture toughness J C of bi‐material interfaces decrease. The constraint parameter A d * values of bi‐material interface cracks are basically independent of the strength and hardening mismatches. A general correlation equation between fracture toughness J C and constraint parameter A d * has been obtained, which may be applied to prediction of fracture toughness of any specimens or components with different geometric constraints and material properties mismatches (including homogeneous materials). The prediction capability of the correlation equation has been validated by experimental fracture toughness data of cracks with different strength and hardening mismatches in dissimilar metal welded joints. Highlights: Correlation between fracture toughness and constraint of bi‐material interfaces is studied. The constraint parameter A d * of bi‐material interface is independent of the mismatches. A general correlation equation between fracture toughness and parameter A d * is obtained. Prediction capability of the equation for fracture toughness is validated by experimental data.